(untitled) (International Journal of Physiotherapy, 2016)
Background: Back pain is the common musculoskeletal condition with a high prevalence of up to 80% among the general and work force population at some times in their lives.Muscular injury, fatigue, or facet or disc degeneration can compromise the stabilizing effects resulting in shearing forces that cause pain.Abdominal drawing in maneuver is used to facilitate the re-education of neuromuscular control mechanisms provided by local stabilizing muscles. Objective of the study is to measure the gait parameters and pain control before and after abdominal drawing in maneuver in patient with chronic mechanical low back pain. Methods: Total number of 30 consecutive patients and they were divided into two groups by purposive sampling. Group A is subjects with low back pain and Group B is subjects without low back pain. Outcome measures were average step cycle, average step length, coefficient of variation, time on each foot, Ambulation index measured with Biodex gait trainer. Pain is measured with Revised-Oswestry low back pain questionnaire. Results: Significant difference between gait parameters were observed in both low back pain group and the group without low back pain group with abdominal drawing in maneuver and the changes without abdominal drawing in maneuver was minimal. There was no significant difference found between both groups with or without abdominal drawing in maneuver. Conclusion: Gait parameters and Pain control can be improved by training with abdominal drawing in maneuver thereby it reduces pain and improves gait symmetry in subjects with low back pain.